TRANSPARENCY AND LEGAL CERTAINTY IN WAITING TIME FEES: A CASE STUDY OF MAXIM IN PALU CITY - Fatmawati, Nining; Febryani, Dea Nathaya; Hikmawati, Nurul; Nurfadlillah, Nurfadlillah (Tadayun: Jurnal Hukum Ekonomi Syariah, 2025)
As a socio-financial practice in Indonesia, arisan (a rotating savings and credit association, ROSCA) is increasingly moving to digital and prize-based formats, heightening the risk of contractual ambiguity (gharar) and demanding stronger governance. This study maps contemporary arisan variants in Bobo Village, identifies the forms and degrees of gharar, and formulates mitigation strategies to keep arisan valid under fiqh muamalah. Using an empirical legal (socio-legal) case study supported by doctrinal analysis, we collected primary data through observation and in-depth interviews with participants and community leaders, and secondary data from the literature. Thematic analysis reveals three interlocking risks: uncertainty over post-disbursement installments by early recipients, a risk imbalance borne by late-turn members, and speculative participation. These conditions shift gharar from tolerable (yasir) to excessive (fahish) when turn order, contribution amounts and timing, payout object, and default remedies are unspecified or hard to enforce. We propose a practical, Sharia-aligned mitigation bundle: detailed written agreements, upfront transparency with periodic reporting, simple digital tools with an audit trail, need-based prioritization via musyawarah, and targeted Sharia literacy. The study contributes a typology of gharar triggers specific to Indonesian arisan and an operational checklist for organizers and participants. Abstrak Sebagai praktik sosial-keuangan di Indonesia, arisan kian bergeser ke format digital dan berbasis hadiah, sehingga meningkatkan risiko ketidakjelasan akad (gharar) dan menuntut tata kelola yang lebih kuat. Penelitian ini memetakan varian arisan kontemporer di Desa Bobo, mengidentifikasi bentuk dan derajat gharar yang muncul, serta merumuskan strategi mitigasi agar arisan tetap sah menurut fiqh muamalah. Metode yang digunakan ialah studi kasus sosio-legal yang didukung analisis doktrinal; data primer diperoleh melalui observasi dan wawancara mendalam dengan peserta serta tokoh masyarakat, sedangkan data sekunder berasal dari literatur. Analisis tematikmenemukan tiga risiko yang saling terkait: ketidakpastian kelanjutan iuran pascapencairan oleh penerima awal, ketimpangan risiko pada anggota yang menerima giliran akhir, dan partisipasi bernuansa spekulatif. Kondisi ini menggeser gharar dari yang ditoleransi (yasir) menjadi berlebihan (fahish) ketika urutan giliran, besaran/waktu iuran, objek pencairan, dan sanksi wanprestasi tidak tegas atau sulit ditegakkan. Peneliti mengusulkan paket mitigasi berbasis syariah: perjanjian tertulis rinci, transparansi dan pelaporan berkala, alat digital berjejak audit, prioritas kebutuhan melalui musyawarah, serta literasi syariah. Kontribusi studi ini berupa tipologi pemicu gharar khusus arisan Indonesia dan daftar periksa operasional bagi penyelenggara/peserta.